Application of the Electro-Electrodialysis Technology in the Copper Mineral Processing Industry: Recovery of Antimony from Mining Tailings and Recycling of the Regenerated Solution Media - Manuel César Martí-Calatayud; Lorena Hernández-Pérez; Andréa Moura Bernardes; Marco Antônio Siqueira Rodrigues; Gerardo Cifuentes; Gabriel Riveros; Valentín Pérez-Herranz (Materials Proceedings, 2023)
In this work, electrodialysis (ED) and electro-electrodialysis (EED) were investigated as technologies for the recovery of Sb from wastes and effluents generated during the pyrometallurgical processing of copper sulfide minerals and the hydrometallurgical treatment of low-copper-content mixed minerals. This work addresses the challenge of applying electrochemical methods for recovering these valuable materials and recycling highly concentrated acid solutions used in the latter separation stages of the electrorefining process. The electrochemical characterization of the solutions was conducted, and the electrodeposition of Sb and Bi was performed in electrochemical cells. Also, the implementation of membrane processes in the recovery of such materials was investigated.